Technical Efficiency of Rice-Based Farming Systems Under Selected Soil Conservation Practices in Ogun State, Nigeria - Ologbon, O. A. C.; Awotide, D. O.; Otunaiya, A. O.; Idowu, A. O. (NIU Journal of Humanities, 2018)
Technical efficiency in rice–based farming systems was estimated and compared for high- and low-level adopters of selected soil conservation practices in Ogun State, Nigeria. Primary data collected from 260 rice farmers in three (3) prominent rice-producing LGAs in Ogun State were analysed and results presented. Multistage sampling techniques were used to select the communities where the data were collected. Four methods of soil conservation technology were commonly practiced in combination in the study area, namely: use of inorganic fertilizers, mulching, shifting cultivation and ploughing back of plant residues into the soil. High- and low-level technology adopters operate at technical efficiency of 70-74% and 40-44%, respectively. For low-level adopters of the selected soil-conservation practices, size of land cultivated (1%); amount of hired labour engaged in production (1%); and the worth of capital invested (5%) will statistically determine the level of rice output. For high-level adopters, worth of capital invested (1%) will influence rice output in addition to land size and amount of hired labour engaged. Quantity of herbicide used (5%) will also statistically determine level of rice output but with a negative influence. Planting local variety of rice cultivar (1%) will statistically increase inefficiency in rice production for high-level adopters as they also tend to use more of inorganic fertilizers to enhance production efficiency (at 5%). Keywords: Technical efficiency, soil conservation, technology adopters, rice cultivars